2019
DOI: 10.1002/col.22428
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network approach for protection of the color of dried golden and pink oyster mushrooms with pretreatments

Abstract: In this study, the possibilities of protecting the color of dried golden and pink mushrooms were investigated, and color parameters of dried mushrooms were modeled by artificial neural network (ANN). For this purpose, first, the golden oyster mushroom (Pleurotus citrinopileatus) and pink oyster mushroom (Pleurotus djamor) were cultivated. Then, pretreatments were applied using citric acid (CA) and potassium metabisulfite (KMS) with different rates (0.5%, 1.0%, and 1.5%) separately, excluding control group mush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…This information is very important in view of the fact that P. citrinopileatus is becoming increasingly popular thanks to its attractive colour and medicinal properties. Moreover, according to literature data, among the coloured mushrooms such as P. citrinopileatus, P. ostreatus, and P. djamor, the P. citrinopileatus strain exhibited the strongest antioxidant activity [80].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This information is very important in view of the fact that P. citrinopileatus is becoming increasingly popular thanks to its attractive colour and medicinal properties. Moreover, according to literature data, among the coloured mushrooms such as P. citrinopileatus, P. ostreatus, and P. djamor, the P. citrinopileatus strain exhibited the strongest antioxidant activity [80].…”
Section: Discussionmentioning
confidence: 91%
“…In turn, citric acid protects mushrooms against browning thanks to its antibacterial and antioxidant properties [71] and it is also used to preserve fruit body colour. Gürgen and Yildiz [80] showed that pretreatment with citric acid in P. citrinopileatus helps to protect their yellow color when fruit bodies were dried. As for malic acid, it is often added to foods as an acidic additive to improve the organoleptic properties of foods [69].…”
Section: Discussionmentioning
confidence: 99%